Landsat time series reveal forest loss and woody encroachment in the Ngorongoro Conservation Area, Tanzania. Issue 6 (15th June 2022) - Borges, Joana; Higginbottom, Thomas P.; Cain, Bradley; Gadiye, Donatus E.; Kisingo, Alex; Jones, Martin; Symeonakis, Elias
Abstract: The Ngorongoro Conservation Area (NCA) of Tanzania, is globally significant for biodiversity conservation due to the presence of iconic fauna, and, since 1959 has been managed as a unique multiple land‐use areas to mutually benefit wildlife and indigenous residents. Understating vegetation dynamics and ongoing land cover change processes in protected areas is important to protect biodiversity and ensure sustainable development. However, land cover changes in savannahs are especially difficult, as changes are often long‐term and subtle. Here, we demonstrate a Landsat‐based monitoring strategy incorporating (i) regression‐based unmixing for the accurate mapping of the fraction of the different land cover types, and (ii) a combination of linear regression and the BFAST trend break analysis technique for mapping and quantifying land cover changes. Using Google Earth Pro and the EnMap‐Box software, the fractional cover of the main land cover types of the NCA were accurately mapped for the first time, namely bareland, bushland, cropland, forest, grassland, montane heath, shrubland, water and woodland. Our results show that the main changes occurring in the NCA are the degradation of upland forests into bushland: we exemplify this with a case study in the Lerai Forest; and found declines in grassland and co‐incident increases in shrubland in the Serengeti Plains, suggesting woody encroachment. These changes threaten the wellbeing of livestock, the livelihoods of resident pastoralists and of the wildlife dependent on these grazing areas. Some of the land cover changes may be occurring naturally and caused by herbivory, rainfall patterns and vegetation succession, but many are linked to human activity, specifically, management policies, tourism development and the increase in human population and livestock. Our study provides for the first time much needed and highly accurate information on long‐term land cover changes in the NCA that can support the sustainable management and conservation of this unique UNESCO World Heritage Site. Abstract : The Ngorongoro Conservation Area (NCA), a UNESCO World Heritage Site, is globally important for biodiversity conservation due to the presence of iconic megafauna. For decades now, the NCA is experiencing a number of notoriously difficult to address challenges; understanding its land cover dynamics is therefore increasingly important to improve habitat monitoring, preserve biodiversity and ensure sustainable development. We used multi‐temporal Landsat data spanning 35 years and a combination of regression‐based unmixing, linear regression and a trend break analysis to map and quantify the land cover dynamics in the area. We found a decrease in forest and grassland cover as well as a significant amount of woody encroachment which is often linked to land degradation in African savannahs. These changes are consistent with other savannah ecosystems and pose a threat to the wellbeing of livestock, the livelihoods of the pastoralist communities, and the wildlife of the NCA.